Simulation studies of combustion in a constant-mass variable-volume combustion chamber - Anetor Lucky; Osakue Edward E. (FME Transactions, 2018)
A numerical simulation code was used to conduct a systematic study of the effects of fuel-air equivalence ratios in the range 0.7 ≤ φ ≤ 1.4 and compression ratio, rc = 8.0 on key operating parameters, such as pressure, rate of change of pressure, '/dt' flame extinction temperature, burn rate frequency, combustion efficiency, ηb, source term, mass burn fractions and heat loss in a simulated 5.734 liter, V8 spark-ignition engine. The data shows that the burn rate characteristics of the fuel and oxidizer are qualitatively perfectly correlated. The results also show that as flame extinction/flameout is approached, the fuel consumption rate, Rfu increases rapidly with temperature for fuel-air equivalence ratios, φ in the range 0.7 ≤ φ ≤ 1.4. The average burn rate frequency (per second), fbr(1/s) varies from 11.2 ≤ fbr ≤ 137.0 for fuel-air equivalence ratios, φ in the range 0.7 ≤ φ ≤ 1.4 The results further show that the fastest fuel consumption rate was for fuel-air equivalence ratio, φ = 1.4 in the time interval, t such that 0.0 ≤ t ≤ 0.61 ms while the slowest corresponds to φ - 0.7 and the corresponding time interval was 0.0 ≤ t ≤ 3.98 ms. Moreover, the data shows that for fuel-air equivalence ratios, φ in the range 0.7 ≤ φ ≤ 1.4 the fuel consumption rate increases monotonically after the initial ignition delay period. The combustion efficiency, ηb of the engine under investigation were found to be in the range of 94.1% ≤ ηb ≤ 94.4% for lean mixtures, that is, for φ < 1.0;the corresponding values of combustion efficiency, ηb for fuel-rich mixtures were in the interval 93.8% ≤ ηb ≤ 94.1%. The other results from this study are summarized in the conclusion.